1995
DOI: 10.1111/j.1600-0897.1995.tb00968.x
|View full text |Cite
|
Sign up to set email alerts
|

IL‐1β TNF‐α, and IL‐2 in Peritoneal Fluid and Macrophage‐Conditioned Media of Women With Endometriosis

Abstract: This study supports the concept that endometriosis is associated with activation of peritoneal macrophages, and a higher concentration of these cells. This activation is reflected by the increased levels of cytokines found in macrophage conditioned media. The absence of significant changes in peritoneal fluid cytokine levels would seen to indicate that the above derangements are not responsible for the development or progression of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
2
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(77 citation statements)
references
References 19 publications
2
71
2
2
Order By: Relevance
“…Accumulating evidence supports the notion that the progression of endometriotic lesions is catalyzed by an aberrant immune response noted in the peritoneal cavity of women with endometriosis (23)(24)(25)(26)(27)(28)(29)(30). It is uncertain if the initial development of the disease is related to this inflammatory response.…”
Section: Discussionmentioning
confidence: 81%
“…Accumulating evidence supports the notion that the progression of endometriotic lesions is catalyzed by an aberrant immune response noted in the peritoneal cavity of women with endometriosis (23)(24)(25)(26)(27)(28)(29)(30). It is uncertain if the initial development of the disease is related to this inflammatory response.…”
Section: Discussionmentioning
confidence: 81%
“…Activated PMs can release a variety of cytokines, such as interleukin (IL)-1β and IL-6, into the peritoneal fluid and serum. These cytokines are involved in the pathophysiology of endometriosis [5][6][7].…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Peritoneal fluid from patients with endometriosis has frequently been shown to be toxic to the preimplantation embryo. A study demonstrated that medical treatment of endometriosis eliminated the embryotoxicity of the peritoneal fluid (Keenan et al,1995). In this study, the levels of IL-1 and TNF-were markedly reduced in the peritoneal fluid of women who had undergone medical treatment (danazol or intranasal buserelin for 4 to 6 months) of endometriosis.…”
Section: Cytokines and Endometriosis Related To Infertilitymentioning
confidence: 66%